Problematika Perkawinan di Kalangan Mahasiswa dalam Membentuk Keluarga Sakinah - Ridhowan, M.; Assegaf, Assegaf; Sholihudin, Sholihudin (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
Marriage is usually carried out by people who are mature and ready psychologically and economically. However, it is not uncommon for students to do it which often creates problems both psychologically and economically. The purpose of this study was to find out the problems of marriage among students in forming a sakinah family at the Institut Pesantren Sunan Drajat Lamongan. Data collection techniques using observation, interviews, and documentation. As for data analysis using descriptive qualitative analysis. The results showed that the phenomenon experienced by married students of the Institut Pesantren Sunan Drajat Lamongan, they experienced many problems, such as economic, academic or educational problems, and relationship problems between families.